2023
DOI: 10.3389/fimmu.2023.1173728
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the systemic anticancer immune environment in tumour-bearing humanized mouse by using liposome-encapsulated anti-programmed death ligand 1 antibody-conjugated progesterone

Yoshie Kametani,
Ryoji Ito,
Shino Ohshima
et al.

Abstract: Immune checkpoint inhibitors highlight the importance of anticancer immunity. However, their clinical utility and safety are limited by the low response rates and adverse effects. We focused on progesterone (P4), a hormone produced by the placenta during pregnancy, because it has multiple biological activities related to anticancer and immune regulation effects. P4 has a reversible immune regulatory function distinct from that of the stress hormone cortisol, which may drive irreversible immune suppression that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Lipo-P4 and empty control liposomes (Lipo-Emps) were prepared as described previously [ 13 ]. Details are provided in the Supplemental Materials.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lipo-P4 and empty control liposomes (Lipo-Emps) were prepared as described previously [ 13 ]. Details are provided in the Supplemental Materials.…”
Section: Methodsmentioning
confidence: 99%
“…Human PBMCs (5 × 10 6 cells) were intravenously injected into 8-week-old NOG-hIL-4-Tg mice (hu-PBL NOG-IL-4-Tg mice). Female mice were used, while previous studies with hu-PBL NOG IL-4-Tg mice showed no influence of sex with respect to the lymphocyte engraftment [ 13 , 19 ]. On the same day, Lipo-anti-PD-L1-P4 was administered intraperitoneally, and this treatment continued every five days, for a total of six times.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations